Autonomie z pohledu seniorů - Truhlářová, Zuzana; Vosečková, Alena (Univerzita Pardubice, 2013)
Personal autonomy and respect for personal autonomy is the right of every human being in every period of his/her life. The objective of this scientific essay is to answer the question: first of how the seniors see themselves as autonomous persons in terms of physical state and financial situation, and second of how the seniors perceive self-sufficiency in terms of individual decision. Almost all scientific publications in the field of senior population deal with the elderly in institutional care and/or with the seniors who depend on the care of others. Our report focuses on the seniors living in a natural environment (family). It aims to map the views and opinions of a relatively self-sufficient, very large group of seniors who we can meet in the streets today and who we are likely to meet more often in the future. The goal of the research is to assess the perceived autonomy among elderly subjects in terms of physical self-sufficiency. The point is not to create a statistical data analysis and/or hypothesis testing but to map a significance of subjective health for the perceived autonomy among the seniors.
Autonomy from the perspective of seniors
Keywords: autonomy; physical health; seniors; subjective health; self-sufficiency